Bridging The Gap: Reconciling Privacy Data Protection With Indonesian Collectivism - Moch. Marsa Taufiqurrohman; Tarsisius Murwadji; Helza Nova Lita (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
This article analyzes the interplay between Indonesia’s collectivist cultural values and the implementation of Law No. 27 of 2022 on Personal Data Protection (Law No. 27/2022). The Law faces significant challenges in a society where awareness of data privacy remains low. This article utilizes a socio-legal research methodology to explore the cultural factors influencing Indonesian societal attitudes and behaviors towards data privacy. The article begins by outlining the core regulatory framework of Law No. 27/2022, comparing its implementation within individualistic and collectivist contexts. It highlights the inherent tension between the Law’s emphasis on individual data rights and Indonesia’s deeply ingrained collectivist values, which prioritize communal harmony and open information sharing. This cultural tendency often overshadows concerns about potential security risks, hindering the Law’s effective implementation. To bridge this gap, the article proposes a “hybrid” approach that integrates international data protection standards with culturally relevant strategies. This includes emphasizing the collective benefits of data protection, framing it as a shared responsibility to protect the community’s well-being. Furthermore, the article stresses the importance of public education campaigns tailored to resonate with Indonesian cultural values. By empowering individuals with knowledge and legal awareness, the article argues that Indonesia can foster a more balanced approach to data protection that respects both individual rights and collective harmony.